Recycling of Rubber Wastes as Fuel and Its Additives - Ahmed Akbas; Nor Yuliana Yuhana (Recycling, 2021)
Economic, social, and urban developments generally require improvements in the transportation sector, which includes automobiles such as trucks, buses, trailers, airplanes, and even bicycles. All these vehicles use rubber tires. After consumption, these tires become waste, leading to enlarged landfill areas for used tires and implying additional harm to the environment. This review summarizes the growth of rubber recycling application and the sustainability of using waste rubber in the construction field. Furthermore, we provide methods to convert rubber waste to fuel or fuel additives by using tire-derived fuel and concentrate to pyrolysis, which are environmentally friendly and efficient ways. The related parameters such as temperature, pressure, and feedstock composition were studied. Most research papers observed that 500 °C is the optimal temperature at atmospheric pressure in the presence of a specific type of catalyst to improve pyrolysis rate, oil yield, and quality.